Comercialização informal de queijo colonial no município de Santa Maria/RS: do consumidor à regulamentação - Braccini, Valéria Pinheiro (2020)
In the southern region of Brazil, most artisanal cheeses are colonial type. Marketed at fairs in the municipality of Santa Maria, or colonial cheese (QC), on the one hand, appreciated by consumers and, on the other, a discussion agenda on the sanitary and informal quality of the production process. In this scenario, issue this dissertation which has two main objectives divided into article format. The first seeks to understand the motivations of colonial cheeses that support informality and understand what rules (formal or information) that allow and legitimize interactions between consumers and producers in the three markets in the municipality of Santa Maria / RS.This study has a descriptive, exploratory and quantitative approach with the application of a questionnaire to 111 consumers in the municipality. The data were submitted to non-parametric tests and univariate statistical analysis, using the PSPP software with significance less than or equal (≤) to 0.05 in the chi-square test. Correlations were found in the three groups of variables studied: cultural aspects and beliefs; cultural aspects and health legislation; and, health legislation and beliefs. In the end, the hypothesis is confirmed that despite the State's effort to regulate the marketing of QC, informality persists because the producer finds support in the consumption tradition, with predominance of the rules of the informal environment. The second article aims to identify the institutionalization of the ARTE seal in the municipality of Santa Maria / RS, comprising the articulations for the implementation of Decree nº 9.918 / 19. The methodology used involves the bibliographic review (focused on Institutional Theory and its pillars) and research of field, with semi-structured interview with informants (technicians from EMATER / RS - ASCAR and agricultural inspectors from the State and Municipality). It appears that, in the initial phase, the process is under the regulatory and cultural cognitive pillars, expressed by the new public policy, which coordinates as actions of the criteria and rules defined to regulate as future actions and by the way they interpret and react to the implantation of the ARTE label, questioning its innovative character, respectively. A coercive isomorphic pressure is imposed on it, represented by the government pressure of the ARTE seal. In the habitualization phase, identify the normative and cognitive cultural pillars, due to the resistance of the fiscal bodies, regarding the orientative and educational functions and observe that the normative and cognitive cultural pillars are under the pressure of normative isomorphism. In the objectivity stage, the regulatory and cognitive cultural pillars (considering the determination of Good Agricultural and Manufacturing Practices) and the incidence of normative and mimetic isomorphisms were identified. The sedimentation process was not addressed in this case due to the ARTE Seal and is currently in the process of preparing normative instructions. Finally, it was possible to realize that the ARTE Seal is in the process of institutionalization at the place of study, lacking the methodologies used for an effective implantation.